Iran Economic Monitor, Spring 2020 : Mitigation and Adaptation to Sanctions and the Pandemic - World Bank (World Bank, Washington, DC, 2020)
The recession in Iran accelerated in 2019-20 as United States (U.S.) sanctions further tightened. Inflation has gradually declined as the impact of the sharp depreciation of the rial in 2018-19 dissipated but foreign exchange reserves remain limited. The growing gross borrowing needs has increased the government’s reliance on debt issuance and withdrawals from strategic reserves. Negative economic growth and high inflation coupled with COVID-19 (Coronavirus) will put further pressure on household livelihoods in 2020-21. The current unique situation of Iran’s economy presents significant downside risks for the baseline macroeconomic outlook. The country’s economic and social challenges disproportionately impact the lower income decile households who have faced significant economic pressure. Any increase in the value of cash transfers, along with introducing targeting mechanisms, can help the poor cope with the social-economic shocks, but fiscal constraints may limit the scope for significant response.